(untitled) (Global Journal of Science Frontier Research, 2018)
Performance of different treatments was evaluated to find out effective control measures against some fearsome diseases of farmers stored Chickpea seeds. A set of seven treatments were used in the study: two fungicides (Provax 200WP and bavistin 70WP), two botanical extracts (Neem leaf and Garlic clove), bio-fertilizer, breeder seeds and healthy seeds. All treated seeds including breeder seeds and healthy seeds performed better compared to control. Fungicides successfully inhibited fungal growth in laboratory and field conditions. In blotter method, seeds treated with Provax 200WP and Bavistin 70WP showed the highest results against Fusarium oxysporum, Sclerotium rolfsii and Botrytis cinerea compared to control and all other treatments. In controlling the radial growth of fungi at 100, 200 and 400ppm, Provax 200WP performed the best against Sclerotium rolfsii, Bavistin 70WP against Fusarium oxysporum and both of the treatments performed best against Botrytis cinerea and % inhibition increased with increasing concentrations. Also, the highest plant population and the lowest incidence per pot or plot exhibited with fungicides application, and in some cases, a combination of healthy seeds and Bavistin 70WP showed insignificant results.